Mechanical Property, Efficacy, and User Experience of an Innovative Wearable Device in Preventing Fall-Induced Injuries - Hu, Kaixin; Guan, Zhongyang; He, Zhijie; Luo, Siran; Fang, Hongbin; Zhang, Yan; Ding, Li; Xu, Ying; Jiang, Liuya; Fu, Conghui; Zhao, Xiaoqing; Jia, Jie; et al. (Innovation in aging, 2024)
Abstract Background and Objectives With the global population aging at an unprecedented pace, the imminent surge in falls and fall-induced injuries necessitates urgent attention. Innovative assistive technologies are crucial in addressing this daunting challenge. This study aimed to evaluate the mechanical properties, efficacy, safety, and user experience of the Intelligent Bone Protection Vest (IBPV), a novel, reusable, non-airbag wearable device. Research Design and Methods The IBPV integrates a machine learning-based algorithm for real-time monitoring of wearer motion and a unique honeycomb-structured foldable cushion for fall impact attenuation. We evaluated the impact attenuation capabilities of the IBPV and conducted 2 human subject studies to assess its efficacy and safety. Additionally, semistructured interviews were conducted to qualitatively explore its usability, safety, and opportunities for enhancement. Results The compression tests confirmed the energy absorption capacity of the honeycomb-structured foldable cushion. In over 800 fall tests involving 14 young and middle-aged subjects using a touchdown fall test, as well as 7 older subjects using a novel fall simulation test, the IBPV demonstrated an overall protection rate exceeding 84%. Discussion and Implications These results underscored the potential of the IBPV in reducing fall-induced injuries by mitigating the impact force on the hip during falls. Future studies with more rigorous design are needed to confirm whether this active wearable device may serve as a dependable fall protection product.